2016
DOI: 10.1080/02680939.2016.1145253
|View full text |Cite
|
Sign up to set email alerts
|

Media accounts of school performance: reinforcing dominant practices of accountability

Abstract: Media reportage often act as interpretations of accountability policies thereby making the news media a part of the policy enactment process. Within such a process, their role is that of policy reinforcement rather than policy construction or contestation. This paper draws on the experiences of school leaders in regional Queensland, Australia, and their perceptions of the media frames that are used to report on accountability using school performance. The notion of accountability is theorised in terms of media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 55 publications
(58 reference statements)
1
43
0
1
Order By: Relevance
“…Other related research (Shine, 2015a;Baroutsis and Lingard, 2017;Wallace, 2007) has noted a particular recent focus on testing, performance and accountability in the reporting of education, and a repeated questioning of standards. Consistent with the findings reported here, a recent Australian study (Baroutsis, 2016) that considered news coverage of standardised testing also found that metropolitan news outlets generally framed coverage negatively, while the reporting in local and regional news organisations tended to be more balanced. This may be due to the fact that teachers and/or principals are more likely to have an ongoing relationship with a local or regional news journalist or editor.…”
supporting
confidence: 88%
“…Other related research (Shine, 2015a;Baroutsis and Lingard, 2017;Wallace, 2007) has noted a particular recent focus on testing, performance and accountability in the reporting of education, and a repeated questioning of standards. Consistent with the findings reported here, a recent Australian study (Baroutsis, 2016) that considered news coverage of standardised testing also found that metropolitan news outlets generally framed coverage negatively, while the reporting in local and regional news organisations tended to be more balanced. This may be due to the fact that teachers and/or principals are more likely to have an ongoing relationship with a local or regional news journalist or editor.…”
supporting
confidence: 88%
“…The first two phrases aspire to the more democratic notions of the free press (Finkelstein & Ricketson, 2012) acting as society's guardian and holding power to account; while the latter is about influence. These are common understandings by media practitioners of the role of media (see Baroutsis, 2016). For example, a recent review of media in Australia, the Finkelstein Inquiry, 1 identified a role of media as being society's guardians (Finkelstein & Ricketson, 2012).…”
Section: Agendisation and Accountabilisationmentioning
confidence: 99%
“…These practices seek to influence politics and policy (Birks, 2010). However, within this agenda-setting context, newspapers, editors, and journalists perceive their media role as that of policy reinforcement, rather than policy construction or contestation (Baroutsis, 2016).…”
Section: Australian Media Coverage Of Pisamentioning
confidence: 99%
“…While our study is Australian in focus, it has relevance in the global policy context because of the strengthening global policy significance of PISA (Sellar & Lingard, 2014) and enhanced salience of the media in policy (Lingard & Rawolle, 2004;Baroutsis, 2016). As Blackmore and Thorpe (2003) state:…”
Section: Introductionmentioning
confidence: 95%